Implementation of Inclusive Education in Regular School: Narrative Literature Review - Zain, Zuhra Fadlulla; Yoenanto, Nono Hery; Fardana N, Nur Aini (JPI (Jurnal Pendidikan Inklusi), 2021)
This literature study aims to describe the implementation of inclusive education in regular schools in Indonesia along with the challenges and advantages in its implementation. The selection of journal articles in this literature study is based on several inclusion and exclusion criteria, namely, articles published in the period 2019-2024 or in the last 5 years except for basic theory, the research location comes from a regular school, the type or research method uses quantitative, qualitative, and mixed methods, and articles in English and Indonesian. Then, the exclusion criteria specified were articles or research that have been published for more than 5 years, research locations that are not from state schools, articles with methods other than quantitative, qualitative and mixed methods, and languages used other than English and Indonesian. Thus, 13 suitable journals were found. The results of this literature study found that the implementation of inclusive education in regular schools still has many shortcomings that need to be addressed. Some of the main problems are the insufficient availability of shadow teachers (or if it's in Indonesian is GPK) and the distribution of aid funds that have not been provided, which has an impact on the development of school facilities and infrastructure. So, by considering several challenges and success factors, it is hoped that this can be taken into consideration in improving and equitable implementation of inclusive education in regular schools in Indonesia. .